COMPUTATIONAL SOLUTION OF TEMPERATURE DISTRIBUTION IN A THIN ROD OVER A GIVEN INTERVAL I=x├|0<x<1┤ - Iyanda, Falade Kazeen; Baoku, Ismail; Ibrahim, Gwanda Yusuf (FUDMA JOURNAL OF SCIENCES, 2021)
In this paper, two analytical–numerical algorithms are formulated based on homotopy perturbation method and new iterative method to obtain numerical solution for temperature distribution in a thin rod over a given finite interval. The effects of different parameters such as the coefficient which accounts for the heat loss and the diffusivity constant are examined when initial temperature distribution (trigonometry and algebraic functions) are considered. The error in both algorithms approaches to zero as the computational length increases. The proposed algorithms have been demonstrated to be quite flexible, robust and accurate. Thus, the algorithms are established as good numerical tools to solve several problems in applied mathematics and other related field of sciences